The Part of Parents in Educating Children to Choose a Life Partner According to Christian Faith - Setiawan, Agus; Hermanto, Yanto Paulus (Sekolah Tinggi Teologi Berita Hidup, 2024)
The phenomenon of interfaith marriage continues to occur in the midst of the plurality of Indonesian society. This of course can affect the faith of young Christians, if they choose the wrong life partner. Parents are obliged to educate their children according to the Christian faith. The choice of a life partner for young Christian youths should be in line with God's design for their lives, so that the future of the new family will inherit the Christian faith. The author conducted library research to collect information about the role of parents in educating children and choosing a life partner according to the Christian faith. The results of the study state that the part of parents is to educate their children to fear God, to be obedient in doing His will, and always to hope and rely on God; will form the divine character in the person of a child. So that in the end they can choose a life partner correctly and can make the decision to commit to marriage, according to the advice of their parents and the leading of the Holy Spirit in their life.